2020
DOI: 10.1158/1940-6207.capr-19-0496
|View full text |Cite
|
Sign up to set email alerts
|

Black Raspberry Inhibits Oral Tumors in Mice Treated with the Tobacco Smoke Constituent Dibenzo(def,p)chrysene Via Genetic and Epigenetic Alterations

Abstract: We previously reported that the environmental pollutant and tobacco smoke constituent dibenzo [def,p]chrysene (DBP) induced DNA damage, altered DNA methylation and induced oral squamous cell carcinoma (OSCC) in mice. In the present study, we showed that 5% dietary black raspberry (BRB) significantly reduced (P < 0.05) the levels of DBP-DNA adducts in the mouse oral cavity with comparable effect to those of its constitutes. Thus, only BRB was selected to examine if aberrant DNA methylation induced by DBP can be… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 47 publications
1
17
0
Order By: Relevance
“…The environmental pollutant and tobacco smoke constituent dibenzo[def,p]chrysene (DBP) was used to induce OSCC in mice and to explore the effects of 5% dietary black raspberry. A reduction in the levels of DBP-DNA adducts in the mouse oral cavity with a comparable effect to those of its constituents was observed [130].…”
Section: In Vivo Studiesmentioning
confidence: 71%
“…The environmental pollutant and tobacco smoke constituent dibenzo[def,p]chrysene (DBP) was used to induce OSCC in mice and to explore the effects of 5% dietary black raspberry. A reduction in the levels of DBP-DNA adducts in the mouse oral cavity with a comparable effect to those of its constituents was observed [130].…”
Section: In Vivo Studiesmentioning
confidence: 71%
“…We showed that BRB reduces oxidative stress in human oral leukoplakia cells [ 25 ]. Furthermore, we demonstrated that BRB inhibited OSCC induced by DBP or DBPDE via genetic and epigenetic alterations [ 15 , 16 ]. We also found that BRB was associated with a significant hypomethylation of the fibroblast growth factors (eg.…”
Section: Discussionmentioning
confidence: 99%
“…Inflammation is also induced in these mice and is exemplified by increases in Cox2 gene expression as well as several inflammatory cytokines such as Ccl22 and Cxcl10 [ 14 ]. Our team also demonstrated that feeding black raspberry (BRB) to both DBP and DBPDE treated mice inhibits tumor formation and altered several molecular targets in a manner consistent with its preventive/therapeutic action for HNSCC [ 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…The study reported that administration of a 5% BRB diet prior to carcinogen exposures resulted in fewer DNA adducts and abrogated tumor incidence from 93% to 66% (Chen et al, 2018). It was later reported that BRB-mediated reduction in oral mutagenesis could be attributed, in part, to epigenetics and hypermethylation of genes involved in epithelial-mesenchymal transition (Chen et al, 2020). These BRB-mediated metabolomic effects in oral cancer are further supported in a study by Knobloch et al (2019), using a chemically-induced model of oral cancer, (4-nitroquinoline-1oxide) (El-Bayoumy et al, 2017), whereby 6-week exposure to a 10% BRB diet inhibited enzymes fundamental for the metabolic pathway of glycolysis, thereby limiting nutrient availability for cancer cells (Knobloch et al, 2019).…”
Section: Chemopreventive Studies Of Black Raspberries In Oral Cancermentioning
confidence: 99%
“…The study reported that administration of a 5% BRB diet prior to carcinogen exposures resulted in fewer DNA adducts and abrogated tumor incidence from 93% to 66% (Chen et al., 2018). It was later reported that BRB‐mediated reduction in oral mutagenesis could be attributed, in part, to epigenetics and hypermethylation of genes involved in epithelial‐mesenchymal transition (Chen et al., 2020). These BRB‐mediated metabolomic effects in oral cancer are further supported in a study by Knobloch et al.…”
Section: Introductionmentioning
confidence: 99%